An imperial harbinger: Sylvester O'Halloran's General history (1778). Issue 155 (May 2015) - Lyons, Claire E.
Abstract: This article investigates the antiquarian response to the opportunity for Irish Catholic relief during the Anglo–American crisis and views Sylvester O'Halloran's General history as an innovative attempt to initiate Irish Catholic participation in the British empire predicated on a historic and current fittingness. The London publication of the General history indicated that this work was directed at an audience outside of, as well as within, Ireland. An investigation of the subscription-list confirms that that audience consisted of members of Britain's political élite and successful émigré Irishmen in the service of European Catholic powers. The narrative analysis, when compared with its principal sources, Keating's seventeenth-century Foras feasa ar Éirinn and the twelfth-century Lebor gabála Érenn, shows that O'Halloran altered his source materials to construct an historical picture of a Milesian maritime empire. O'Halloran's argument for Catholic inclusion in the British empire was twofold. He altered his source material to suggest an ancient parity with the contemporary British empire to demonstrate an Irish historical fittingness for an imperial role, while his subscription-list confirmed a current aptitude. This argument was directed at and partly endorsed by another section of the subscription-list, London's political élite.